2009
DOI: 10.1021/la8030045
|View full text |Cite
|
Sign up to set email alerts
|

A Cassie-Like Law Using Triple Phase Boundary Line Fractions for Faceted Droplets on Chemically Heterogeneous Surfaces

Abstract: We present experimental contact angle data for surfaces, which were surface-engineered with a hydrophobic micropattern of hexagonal geometry. The chemically heterogeneous surface of the same hexagonal pattern of defects resulted in faceted droplets of hexagonal shape. When measuring the advancing contact angles with a viewing position aligned parallel to rows of defects, we found that an area averaged Cassie-law failed in describing the data. By replacing the area fractions by line fractions of the triple phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 15 publications
2
58
0
Order By: Relevance
“…It should be mentioned that dependence of the APCA on equilibrium contact angles on the hierarchical surfaces is weak when compared with those on single-scale surfaces (Bormashenko et al 2008b). Modifications of the Cassie-Baxter equation that take into account the peculiarities of the complicated topography of biomimetic surfaces were reported recently (Nosonovsky & Bhushan 2008;Choi et al 2009;Larsen & Taboryski 2009). …”
Section: Wetting Statesmentioning
confidence: 99%
“…It should be mentioned that dependence of the APCA on equilibrium contact angles on the hierarchical surfaces is weak when compared with those on single-scale surfaces (Bormashenko et al 2008b). Modifications of the Cassie-Baxter equation that take into account the peculiarities of the complicated topography of biomimetic surfaces were reported recently (Nosonovsky & Bhushan 2008;Choi et al 2009;Larsen & Taboryski 2009). …”
Section: Wetting Statesmentioning
confidence: 99%
“…Their 2009 report investigated the wetting mechanism using a patterned hydrophilic substrate with hydrophobic defects (Figure 18). 253 This situation is opposite that encountered on fresh graphite (mildly hydrophilic surface with defects that are more hydrophilic) although the wetting mechanism remains similar for both situations. A quick glance at Figure 18a shows that the water contact line is irregular and not symmetrical.…”
Section: -248mentioning
confidence: 92%
“…Nearly all of the most recent work done to elucidate the causes of hysteresis have sought to explain phenomena surrounding superhydrophobic surfaces; therefore, they use micropatterned surfaces with a repetitive pillar array. 251,[253][254][255][256] The pillars are typically on the micron scale and range from a few to several microns in height, width, and spacing. When a water drop is placed on this micropatterned surface, it will interact with a composite surface of (1) the pillars and (2) Larsen and Taboryski studied the behaviour of hysteresis on chemically heterogeneous surfaces and showed that the contact line is distorted by defects and behaviour of the advancing and receding contact angle is dependent on surface wetting compared to defect wetting.…”
Section: -248mentioning
confidence: 99%
See 2 more Smart Citations